HDMS-YOLO: a multi-scale weed detection model for complex farmland environments - Hua, Jing; He, Ruimin; Zeng, Yanhua; Chen, Qi (Frontiers in Plant Science, 2025)
IntroductionWith the continuous advancement of agricultural technology, automatic weed removal has become increasingly important for precision agriculture. However, accurate weed identification remains challenging due to the diversity and varying sizes of weeds, as well as the high visual similarity between weeds and crops in terms of shape, colour, and texture.MethodsTo address these challenges, this study proposes the HDMS-YOLO model for robust weed identification, trained and evaluated on the publicly available CropAndWeed dataset. The model incorporates two novel feature extraction modules—the Shallow and Deep Receptive Field Distillation (SRFD and DRFD) modules—to effectively capture both shallow and deep weed features. The traditional C3K2 structure is replaced by the Partial Convolution-based Multi-Scale Feature Aggregation (PC-MSFA) module, which enhances feature representation through partial convolution and residual connections. In addition, a new IntegraDet dynamic task-alignment detection head is designed to further improve localisation and classification accuracy.ResultsExperimental results show that HDMS-YOLO achieves an accuracy of 74.2%, a recall of 66.3%, and an mAP of 71.2%, which are 2.6%, 2.1%, and 2.6% higher, respectively, than those of YOLO11. Compared with other mainstream algorithms, HDMS-YOLO demonstrates superior overall detection performance.DiscussionThe proposed HDMS-YOLO model exhibits strong capability in extracting and representing weed features, leading to improved identification accuracy and generalisation. These results highlight its potential application in precision farm management and the development of intelligent weed-removal robots for unmanned agricultural systems.